A Preliminary Characterisation of Cognition and Social Cognition in Spinocerebellar Ataxia Types 2, 1, and 7 - N. Sokolovsky; A. Cook; H. Hunt; P. Giunti; L. Cipolotti (Behavioural Neurology)
Over the last decade, studies have implicated the cerebellum not only in motor functioning, but also in cognition and social cognition. Although some aspects of cognition have been explored in the five most common forms of Spinocerebellar Ataxia (SCA), social cognition in these patients has rarely been examined. The present study provides a preliminary characterisation of the severity of cognitive and social cognitive impairments in patients with SCA2, SCA1 and SCA7 using an identical battery to the one previously used in SCA3 and SCA6 patients for comparison. The cognitive profiles of SCA1 and SCA7 patients were comparable to that of SCA6 patients; SCA1 patients had relatively intact profiles, while SCA7 patients demonstrated only some selective deficits. In contrast, SCA2 patients showed the greatest impairments, similarly to SCA3 patients. On tests of social cognition, SCA2 and SCA7 patients were impaired on a task of emotion attribution, whereas one SCA1 patient had a Theory of Mind deficit, which has also been documented in SCA3 and SCA6. We provide preliminary evidence that the neuropsychological profiles of SCA patients correspond well with the severity of pathological and clinical features. Moreover, these patients may also have social cognition impairments. Overall, we suggest that there is a degree of heterogeneity in the types of cognitive and social cognitive impairments in SCA patients.